FORMATION OF LOW TC SUPERCONDUCTING PHASE IN BSCCO SYSTEM - Qayyum, S.; Durrani, S. K.; Akhtar, J.; Qureshi, A. H.; Arif, M.; Ahmed, M.; Rahman, S. (The Nucleus, 2020)
The sol spray process (modified form of sol gel) has been used to prepare Bi-Sr-Ca-Cu-O (BSCCO) homogeneous powder. In sol spray process, the prepared sol solutions have been dehydrated directly into BSCCO ceramic powder by spraying into a preheated temperature controlled pyrex glass column by means of compressed air atomization without the addition of organic chelating agent or organic templates. The prepared BSCCO material was characterized by thermogravimetric (TG), differential thermal analysis (DTA), X-ray diffraction (XRD), scanning electron microscopy (SEM) techniques. Elemental compositions of BSCCO oxide powder and calcined pellet were verified by inductively coupled plasma emission spectrometer (ICP-OES) and electron probe micro analyzer (EPMA) attached with SEM. The results of these techniques were compared and correlated statistically. Student t-test and variance ratio test (F-test) were performed for the significance of results by analysis of variance (ANOVA). The dependence of electrical resistance versus temperature was recorded by classical four probe technique. It has been observed that sol spray process did affect the physico-chemical properties of BSCCO superconductor oxide. The superconducting phase identified by above mentioned techniques mainly shows the higher %age of low Tc phase Bi2Sr2CaCu2O8 (2212) with transition temperature of 85 K.